Kuwait's politics before independence : the role of the balancing powers - Alebrahim, Abdulrahman (Exeter critical Gulf series, 2019)
This book re-examines the historiography of constitutional development in Kuwait. It argues that existing scholarship on the subject has several shortcomings due to the lack of consideration given to the role played by some important social forces in the Kuwaiti political scene. Most historians working on Kuwait's modern politics have focussed on two forces: the ruling family and the merchants. Although these two actors have undeniably been the most influential, other segments of society, such as the labour force, the villagers, the intelligentsia and the religious scholars, should not be overlooked. These forces have had a decisive impact, with varying levels of influence across time, on the balance of power in Kuwait. This book generates new insights by considering the role of these balancing forces in influencing the struggle between the sheikhs and the merchants over the nature of the political system in Kuwait between 1921 and 1962. --